Muhammad Iqbal’s Islamic Philosophy Concept of Education Contextualised in Facing the Disruptive Era - Chair, Badrul Munir (‘Abqari Journal, 2021)
This article describes the Muhammad Iqbal’s Islamic philosophy concept of education contextualised in facing the disruptive era. Contextualise thought of Muhammad Iqbal’s Islamic philosophy of education is very necessary because the industrial revolution always bring impact to human life, no exception in the field of education. The important points of Iqbal’s decription of individuality, individual development, alignment between the material and the spiritual, and creativity in education are particularly relevant to our educational conditions today. For Iqbal, the main educational purpose is to stengthen individuality so that everyone is able to understand the own potensiality. The development of individuality is a process in which humans must play an active role by conducting various experiments tha are relevant to the spirit of the times. The spirit of the disruptive era is the spirit of experimentation. But educational experiments, according to Iqbal will always have a moral and spiritual impact. So academics should not ignore the spiritual side of education.